Marketing strategy of Alza.cz a.s. - Matoušek, Martin; Zlatić, Marija; Volfová, Jitka, 1982-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2022)
The first part of the bachelor thesis focuses on the theory of marketing and marketing strategies. The second part is devoted to the survey of the company Alza.cz a.s. in terms of marketing strategy and its possible prospects for the future. In the third part, methodological research in the form of a questionnaire survey is processed and interpreted, which is then evaluated in the form of a recommendation.
Vedoucí práce: Marija Zlatić
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses